INFLUENCE OF FRUIT CHARACTERISTICS ON SEEDS AND SEEDLING EMERGENCE OF FLUTED PUMPKIN (Telfairia occidentalis Hook F.) - U. P. Chukwudi; C. U. Agbo (Journal of Animal and Plant Sciences, 2014)
The positive influence of fruit characteristics on seed and seedling emergence in fluted pumpkin will increase productivity and enhance selection of fruits for sowing. A study was carried out to determine the relationships between the fruit characteristics and seed quality in fluted pumpkin. Three different sizes of fluted pumpkin fruits were obtained from six localities in Enugu state, Nigeria. The study was a 3×6 factorial in completely randomized design (CRD) replicated three times. Analysis of variance was carried out on the fruit and seed characteristics as well as seedling emergence. Pearson’s correlation coefficients and Path coefficients analysis were also determined on the data collected. Large sized fruits were significantly (P<0.05) higher in all the parameters measured except in the number of unfilled seeds and seedling emergence percentage. Fruits from Ibagwa-aka gave significantly (P<0.05) higher seedling emergence (86.8 %) than other accessions. Lowest seed weight and seed size were obtained from Ozalla accessions which also gave the highest number of filled seeds/fruit. All the traits showed positive and highly significant correlation with fruit length, fruit circumference and fruit cavity diameter except number of unfilled seeds which showed negative correlation. Fruit cavity diameter had the highest and positive significant correlation of 0.34 with seedling emergence. Total number of seeds/fruit had the highest direct positive effect of 0.667 on the seedling emergence followed by fruit cavity diameter. It was conclusive from the study that large sized fruits gave higher seed sizes but medium sized fruits gave higher emergence rate and should be selected in favour of the small sized fruits.
Keywords: Fruit size; seedling emergence; seeds; selection; Telfairia